Can Oxidative Stress Induced by Obstructive Jaundice be Improved by Iloprost? An Experimental Study in Rats (International Journal of Scientific Research and Management (IJSRM), 2019)
Background/Aims: Iloprost is a synthetic analogue of epoprostenol which is synthesized by endotelial cells from arachidonic acid. We aimed to evaluate presumed hepatoprotective and antioxidant effects of iloprost in experimentally created obstructive jaundice in rats. Materials and Methods: Thirty-two adult male Wistar albino rats were randomly divided into four groups: sham group (S) (n=8); after sham operation, iloprost administered (SI) group (n = 8); obstructive jaundice (OJ) group (n=8); iloprost administered and obstructive jaundice group (OJI) (n=8). The rats were sacrified ten days after the induction of obstructive jaundice. Blood levels of isoprostane, protein carbonyl, lipid hydroperoxide and 8-hydroxy-2-deoxyguanosine (8-OHdG) were measured. Results: Levels of the oxidative stress products including protein carbonyl [mean, (40.46 versus 24.7 nmol/ml, p=0.005)], lipid hydroperoxide [mean, (5.11 versus 1.85 Mmol/ml,p=0.001)] and 8-OHdG[mean, (1.53 versus 1.13 ng/ml, p=0.03)] in the OJI group were significantly lower than the OJ group. Conclusion: Iloprost supports antioxidant activity in obstructive jaundice without causing further liver damage in rats.